Socio-environmental profile of elderly people from a Matogrossense Pantanal region: A study of endoparasitises (Research, Society and Development, 2021)
Like the natural aging process, the elderly person presents morphophysiological and immunological changes, making parasitic infections more susceptible. Endoparasitoses are a public health problem in Brazil, varying according to basic sanitation conditions, socioeconomic level, education level, age and hygiene habits, among other variables. The general objective of this work was to analyze the prevalence of endoparasites in elderly people who frequent the Centro de Convivência and the elderly and employees of the Long Term Care Institution in the municipality of Cáceres-MT. The samples were analyzed using three laboratory techniques, namely: Hoffmann, Ritchie and modified Safranina staining technique, in the Laboratory of Parasitic Biology  at the State University of Mato Grosso (UNEMAT). THEprevalence of intestinal parasites among the elderly at the Community Center (46.98%), the elderly at the Long Term Care Institution (83.33%) and employees (84.61%). The endoparasites Criptosporidium sp., Cyclospora sp. and Giardia lamblia were the most prevalent, with 22%, 19% and 18%, respectively. This study also evaluated the sociodemographic characteristics and personal hygiene habits of the elderly at the Centro de Convivência and ILP employees. The results suggested a worrying epidemiological condition of the elderly population of the ILP because the high prevalence rates both in the elderly and in the employees show the high risk of infection and reinfection in this environment. and shows the need for educational programs for awareness of hygienic practices and primary health care for the elderly population in these institutions.